60-72 Aylık Çocukların Öz Düzenleme Becerisi Üzerinde Çocuk Katılımlı Eğitim Programının Etkisinin İncelenmesi - ÇELİK, BÜŞRA; KAMARAJ, IŞIK (My University, 2020)
Çocuk Katılımlı Eğitim Programı, Birleşmiş Milletler Çocuk Hakları Sözleşmesi’nin 12. Madde’sinde yer alan “çocuğun katılım hakkı”ndan yola çıkarak hazırlanmıştır. Bu program, Shier’in (2001) “Katılıma Giden Yollar: Açılımlar, Fırsatlar ve Yükümlülükler” adlı makalesinde ele aldığı beş katılım düzeyini temel almakta, doğa ve oyun temalarında 2 proje süreci içeren toplam 15 etkinlikten oluşmaktadır. Bu araştırmada, çocuk katılımını temel alarak hazırlanmış Çocuk Katılımlı Eğitim Programı’na katılan çocukların öz düzenleme becerilerinin, bu programa katılmayan çocuklara oranla daha fazla gelişip gelişmediğinin belirlenmesi amaçlanmıştır. Araştırmada nicel araştırma yöntemlerinden “ön test-son test kontrol gruplu deneysel desen” kullanılmıştır. Araştırmanın çalışma grubunu, 2016-2017 eğitim-öğretim yılında İstanbul’da bulunan bir üniversiteye bağlı anaokulunun iki şubesinde eğitim gören 60-72 aylık yaş grubundan toplam 28 çocuk (14 çocuk deney grubu, 14 çocuk kontrol grubu) oluşturmuştur. Deney ve kontrol grupları seçkisiz atama ile oluşturulmuş, deney grubuna Çocuk Katılımlı Eğitim Programı uygulanmış, kontrol grubuna ise aynı etkinlik türlerini içeren ancak katılım süreçlerini barındırmayan etkinlikler uygulanmıştır. Araştırma için verilerin toplanması; deney ve kontrol gruplarının oluşturulması, çocuklara Demografik Bilgi Formu ve Okul Öncesi Öz Düzenleme Ölçeği’nin (OÖDÖ) öntest olarak uygulanması, Çocuk Katılımlı Eğitim Programı’nın uygulanması ve OÖDÖ’nin sontest olarak uygulanması şeklinde gerçekleştirilmiştir. Araştırmanın sonucunda,

The Child Participation Education Program has been prepared based on the children’s right to participate, which is included in Article 12 of the United Nations Convention on the Rights of the Child. This program is grounded on the five participation levels embraced by Shier (2001) in the article Pathways to Participation: Openings, Opportunities and Obligations and consists of a total of 15 activities including two projects on the themes of nature and play. This study aims to reveal whether or not the self-regulation skills of children who participated in the Child Participation Education Program, which was prepared based on child participation, are more advanced than children who had not participated in the program. It uses the experimental design with pretests and posttests. The study group consists of a total of 28 children (14 in the experimental group, 14 in the control group) between 60-72 months old who are attending school in the 2016-2017 school year. The experimental and control groups have been formed by random assignment, with the Child Participation Education Program being applied to the experimental group and activities containing the same kind of activities without a participation process being applied to the control group. Data have been collected by forming experimental and control groups, applying a demographic information form and the Preschool Self-Regulation Scale to the children as a pretest, applying the Child Participation Education Program to the experimental group, and also applying the same scale as a posttest to all the children. As a result, the study has found the Child Participation Education Program to have an effect on the self-regulation skills of children 60-72 months of age.
An Analysis of the Effect of the Child Participatory Education Program on the Self-Regulation Ability of Children 60-72 Months Old